Compensation of School District Personnel - Bruno, James E. (Management Science, 1971)
Recently considerable attention has been focused on the inadequacy of presently used methods of compensating school district personnel. The increasing incidence of teacher strikes in many school districts has established the need for an effective alternative to the inherent rigidity of the commonly used fixed step salary schedule. The purpose of this study is to propose one such alternative that is based upon mathematical programming techniques. In this study a salary evaluation model was derived then applied to a school district. Salary schedules were derived which (1) were consistent with both the imposed hierarchical and budgetary constraints, (2) considered ten factors in the salary evaluation, and (3) reflected established school district priorities and objectives. This latter feature was accomplished by solving the model with various objective functions.